2010
DOI: 10.1021/ja104791x
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Doped Europium Sulfide

Abstract: We have prepared gadolinium doped europium sulfides, Eu(1-x)Gd(x)S for a doping range of 0 ≤ x ≤ 0.1 by thermal decomposition of the precursors Eu(S(2)CNEt(2))(3)Phen/Gd(S(2)CNEt(2))(3)Phen with respective ratios. Electron doping provides indirect evidence for the magnetic coupling through carrier electrons in magnetic semiconductors. Based on the magnetic properties, we determined that the paramagnetic Curie temperature, Θp, varies with doping level, in a similar way to Eu(1-x)Gd(x)O exhibiting a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…The lattice constants for EuS (5.97Å) and GdS (5.55Å) are close enough that no shift in cell constant was expected or observed in Eu 1−x Gd x S. We measured a sharp increase in the T C and p as a function of doping level, but the data did not fit a smooth function. Our efforts to prepare nanoparticles also did not lead to consistent data [101]. Another report of Eu 1−x Gd x S nanoparticles had beautiful elemental mapping of the nanoparticles using electron energy loss spectroscopy (EELS), which showed that Eu and Gd were uniformly present across each nanoparticle (although core and surface atoms cannot be distinguished in this experiment).…”
Section: Gadolinium Doping (Electrons)mentioning
confidence: 84%
“…The lattice constants for EuS (5.97Å) and GdS (5.55Å) are close enough that no shift in cell constant was expected or observed in Eu 1−x Gd x S. We measured a sharp increase in the T C and p as a function of doping level, but the data did not fit a smooth function. Our efforts to prepare nanoparticles also did not lead to consistent data [101]. Another report of Eu 1−x Gd x S nanoparticles had beautiful elemental mapping of the nanoparticles using electron energy loss spectroscopy (EELS), which showed that Eu and Gd were uniformly present across each nanoparticle (although core and surface atoms cannot be distinguished in this experiment).…”
Section: Gadolinium Doping (Electrons)mentioning
confidence: 84%
“…[19,20] The optical properties of the EuX NCs were rarely reported. Though it has been acknowledged that bulk EuX does not exhibit luminescence at room temperature, [21,22] while surfacemodified EuO and EuS exhibited characteristic luminescence under UV excitation.…”
mentioning
confidence: 99%
“…214,215 Stoll and Jin also studied the enhancement of the Curie temperature of nanosized Gd-ion doped EuS. 201,202 On the basis of those previous reports, the Gd ion can be regarded as an effective dopant for the enhancement of the magnetic properties of EuS crystals. Remarkable magnetic polarona based on the 4f5d exchange interaction of EuO bulk crystals with Gd ions have also been reported.…”
Section: Lanthanoid Nanocrystals VIImentioning
confidence: 98%